COLLABORATION, KNOWLEDGE & THE TRANS-DISCIPLINARY MANAGER: Helping interdisciplinary research projects to flourish - de Vos Malan, Jacques (European Scientific Journal, ESJ, 2013)
Research has been conducted into the special nature of interdisciplinary academic work per se and towards resolving the particular difficulties faced by interdisciplinary researchers. Some of the findings of two recent Australian studies into ways to strengthen interdisciplinary research are reported here. In 2012, the Chief Scientist of Australia commissioned ACOLA to undertake a three-year, 10 million program of research under the title Securing Australia’s Future. The program involves Fellows of the four Australian Learned Academies and embraces issues as diverse as underground engineering for the exploitation of shale gas deposits; how to maximize the translation of innovation and research into productivity; and a critique of the country’s engagement with the Asia-Pacific region. The requirement to deliver at Cabinet level interdisciplinary evidence-based policy options for government, suggests that public policy experience in dealing with “wicked problems” has insights to offer those engaged in interdisciplinary academic research. An emerging group of trans-disciplinary project managers may help interdisciplinary research projects to flourish.